2001
DOI: 10.1097/00001721-200106000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous magnesium does not influence the activity of the coagulation cascade

Abstract: Experimental arterial thrombus formation is reduced during intravenous magnesium infusion. It is well documented that magnesium reduces platelet reactivity, but the antithrombotic effect could also originate from anticoagulant properties or increased fibrinolysis. We therefore evaluated the effect of intravenous magnesium on prothrombin fragment 1 + 2 (F1 + 2), thrombin-antithrombin III complex (TAT) concentrations, and fibrin degradation products (FbDP) in a randomized, cross-over study in 14 healthy voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Some investigators reported that magnesium improved haemostasis or attenuated haemodilution‐induced or postoperative hypercoagulability . However, other studies have shown no difference in coagulation markers or fibrinolytic activity .…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators reported that magnesium improved haemostasis or attenuated haemodilution‐induced or postoperative hypercoagulability . However, other studies have shown no difference in coagulation markers or fibrinolytic activity .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, oral Mg therapy has been shown to reduce platelet-dependent thrombosis by 35% in patients with prior AMI or stroke [140]. The decreased arterial thrombus formation during Mg therapy is related to effects on platelet activity rather than to effects on the coagulation cascade [141]. Finally, Mg can prevent ischemia-reperfusion injury following AMI, a phenomenon discussed in a review elsewhere [142].…”
Section: Cardiovascular-acute Myocardial Infarctionmentioning
confidence: 99%
“…In contrast, Ravn et al. reported that intravenous magnesium had no effect on coagulation factors or fibrinolytic activity [13]. Serebruany et al.…”
mentioning
confidence: 99%